2016
DOI: 10.1186/s12880-016-0151-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of energy spectrum CT for the measurement of thyroid iodine content

Abstract: BackgroundThis study aims to provide a reference for the diagnosis of iodine deficiency disorder by evaluating the normal thyroid iodine content by energy spectrum computed tomography (CT) and calculating the iodine content ratio of thyroid to sternocleidomastoid.MethodsThe thyroid glands of 226 patients were scanned by energy spectrum CT, and the images were analyzed using the GSI Viewer software. Based on the imaging findings, the iodine levels of the thyroid lobes as well as the bilateral sternocleidomastoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…The mean iodine concentration in the thyroid gland with normal thyroid function in the population was 1.31 ± 0.46 mg/ml, which was similar to that of 1.49 ± 0.41 mg/ml measured by gemstone energy spectrum CT imaging technology by Shao Weiguang [5] et al In this study, we found no correlation between thyroid volume and thyroid function. This may be because the thyroid volume can be affected by many factors, such as height, weight, etc.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The mean iodine concentration in the thyroid gland with normal thyroid function in the population was 1.31 ± 0.46 mg/ml, which was similar to that of 1.49 ± 0.41 mg/ml measured by gemstone energy spectrum CT imaging technology by Shao Weiguang [5] et al In this study, we found no correlation between thyroid volume and thyroid function. This may be because the thyroid volume can be affected by many factors, such as height, weight, etc.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies measuring the iodine concentration in phantom have shown that dual energy CT (DECT) is highly accurate in measuring the iodine concentration [3,4]. Shao Weiguang [5] and others proved that gemstone energy spectrum CT imaging made the measurement of iodine concentration more convenient, which can facilitate evaluations of thyroid function. Other studies have also confirmed that thyroid volume measured by CT is relatively accurate [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The mean iodine concentration in the thyroid gland with normal thyroid function in the population was 1.31±0.46 mg/ml, which was similar to that of 1.49±0.41 mg/ml measured by gemstone energy spectrum CT imaging technology by Shao Weiguang [5] et al In this study, we found no correlation between thyroid volume and thyroid function, which may be because the thyroid volume can be affected by many factors, such as height, weight, etc. [11.12] .…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies measuring the iodine concentration in phantom have shown that dual energy CT (DECT) is highly accurate in measuring the iodine concentration [3.4] . Shao Weiguang [5] and others proved that gemstone energy spectrum CT imaging made the measurement of iodine concentration more convenient, which can facilitate evaluations of thyroid function. Other studies have also confirmed that thyroid volume measured by CT is relatively accurate [6.7] .…”
Section: Introductionmentioning
confidence: 99%
“…SpCT tests without iodine contrast agent are not typically performed, so there are limited number of data available. Therefore some researchers tried to estimate iodine concentration in human thyroid tissue [17], or predict extrathyroidal extension and recurrence of PTC [18]. Moreover Bunch et al, in a retrospective study including 20 dual energy parathyroid computed topographies assessed the attenuation of thyroid tissue, parathyroid lesions, and sternocleidomastoid muscle [19].…”
Section: Introductionmentioning
confidence: 99%